The Important of Discipline, Job Satisfaction, and Motivation: Human Resource Development - Mulyadi Mulyadi; Harmita Harmita; Hafidz Maulana; Yelvi Apriandini (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: The manifestation of the potential and human qualities that the organization must possess to achieve its goals include sufficient human resources which can generate and generate ideas, are creative, take the initiative, have problem-solving abilities, and have expertise. Therefore, the purpose of this study was to determine the importance of the variables of motivation, discipline, and job satisfaction in the development of quality human resources. Background Problems: Motivation, work discipline, and job satisfaction are elements that can have an impact on the performance itself. If a person's values are in line with the values supported by the organization, they will feel comfortable working to achieve the organization's goals. Novelty: This study evaluates the similarities and differences between the previous research and the research conducted because the earlier research did not integrate the three variables in one research title. Research Methods: This study uses a review method of six articles and literature studies sourced from various relevant references to the subject matter and research objectives. Findings/Results: Motivation, satisfaction, and work discipline have a significant effect on improving employee performance which will have a direct impact on company performance. Conclusion: The findings of this study indicate that job satisfaction, motivation, and discipline significantly impact performance and positively affect the development of superior human resources.